2020
DOI: 10.1002/chem.202001084
|View full text |Cite
|
Sign up to set email alerts
|

On the Limited Stability of BDPA Radicals

Abstract: 1,3‐Bis(diphenylene)‐2‐phenylallyl (BDPA)‐based radicals are of interest as polarizing agents for dynamic nuclear polarization (DNP). For this purpose, a BDPA‐nitroxide biradical, employing a phosphodiester linkage, was synthesized. Contrary to what is commonly assumed, BDPA‐derived radicals were observed to have limited stability. Hence, the effects of various factors on the stability of BDPA radicals were investigated. Solvent polarity was found to play a significant role on degradation; a polar BDPA radical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…This asymmetry in the EPR line shape is the result of strong e–e (dipolar as well as exchange) couplings indicating the presence of clustered BDPA radicals. In fact, the clustering of BDPA was recently confirmed to occur by a combination of EPR and Mass Spectroscopy measurements, where an instability originating from radical clustering/aggregation was observed with concentrated BDPA and its derivatives (tested up to 30 mM) prepared in a series of organic solvents above −80 °C . As previously discussed by Karabanov et al and later confirmed by Equbal et al, the asymmetric EPR line is one of the distinctive features of TM DNP.…”
mentioning
confidence: 62%
See 2 more Smart Citations
“…This asymmetry in the EPR line shape is the result of strong e–e (dipolar as well as exchange) couplings indicating the presence of clustered BDPA radicals. In fact, the clustering of BDPA was recently confirmed to occur by a combination of EPR and Mass Spectroscopy measurements, where an instability originating from radical clustering/aggregation was observed with concentrated BDPA and its derivatives (tested up to 30 mM) prepared in a series of organic solvents above −80 °C . As previously discussed by Karabanov et al and later confirmed by Equbal et al, the asymmetric EPR line is one of the distinctive features of TM DNP.…”
mentioning
confidence: 62%
“…In fact, the clustering of BDPA was recently confirmed to occur by a combination of EPR and Mass Spectroscopy measurements, where an instability originating from radical clustering/aggregation was observed with concentrated BDPA and its derivatives (tested up to 30 mM) prepared in a series of organic solvents above −80 °C. 37 As previously discussed by Karabanov et al 17 and later confirmed by Equbal et al, 42 the asymmetric EPR line is one of the distinctive features of TM DNP. Asymmetry is necessary to maintain a large polarization gradient across the dipolar broadened EPR line under μw irradiation and to provide a mechanistic basis to induce effective triple-flips that constructively add up to DNP enhancements.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…95,110,123 Addition of water-solubilising carboxylic acid groups in 6 and different amounts of sulfonate groups in 7 (Scheme 5) allowed dynamic nuclear polarization studies in aqueous solutions by Swager et al [124][125][126] The radicals were unaffected by the ionic substituents and their absorption profiles in aqueous solutions closely resembled that of BDPA in dichloromethane solution. 123 BDPA radicals are commonly regarded as air-stable but, recently, Sigurdsson and Mandal 127 revealed that they undergo decomposition under various conditions excluding low temperatures at À80 1C or so. Dimerization was one of the main degradation pathways.…”
Section: For Details)mentioning
confidence: 99%
“…Dimerization was one of the main degradation pathways. BDPA-nitroxide diradicals have been of interest in the dynamic nuclear polarization field, 124,127 and addition of quaternary ammonium groups into BDPA has improved their persistence and made them water-soluble. 128 Swager et al 129 extended the p-conjugation in a planar truxene-based radical 8.…”
Section: For Details)mentioning
confidence: 99%